let A, B be Function of (Polynom-Ring (Polynom-Ring (n,R))),(Polynom-Ring ((n + 1),R)); :: thesis: ( ( for p1 being Polynomial of (Polynom-Ring (n,R))
for p2 being Polynomial of n,R
for p3 being Polynomial of (n + 1),R
for b being bag of n + 1 st p3 = A . p1 & p2 = p1 . (b . n) holds
p3 . b = p2 . (b | n) ) & ( for p1 being Polynomial of (Polynom-Ring (n,R))
for p2 being Polynomial of n,R
for p3 being Polynomial of (n + 1),R
for b being bag of n + 1 st p3 = B . p1 & p2 = p1 . (b . n) holds
p3 . b = p2 . (b | n) ) implies A = B )

set CPN1R = the carrier of (Polynom-Ring ((n + 1),R));
set CPRPNR = the carrier of (Polynom-Ring (Polynom-Ring (n,R)));
set PNR = Polynom-Ring (n,R);
assume A37: for p1 being Polynomial of (Polynom-Ring (n,R))
for p2 being Polynomial of n,R
for p3 being Polynomial of (n + 1),R
for b being bag of n + 1 st p3 = A . p1 & p2 = p1 . (b . n) holds
p3 . b = p2 . (b | n) ; :: thesis: ( ex p1 being Polynomial of (Polynom-Ring (n,R)) ex p2 being Polynomial of n,R ex p3 being Polynomial of (n + 1),R ex b being bag of n + 1 st
( p3 = B . p1 & p2 = p1 . (b . n) & not p3 . b = p2 . (b | n) ) or A = B )

assume A38: for p1 being Polynomial of (Polynom-Ring (n,R))
for p2 being Polynomial of n,R
for p3 being Polynomial of (n + 1),R
for b being bag of n + 1 st p3 = B . p1 & p2 = p1 . (b . n) holds
p3 . b = p2 . (b | n) ; :: thesis: A = B
now :: thesis: for x being object st x in the carrier of (Polynom-Ring (Polynom-Ring (n,R))) holds
A . x = B . x
let x be object ; :: thesis: ( x in the carrier of (Polynom-Ring (Polynom-Ring (n,R))) implies A . x = B . x )
assume A39: x in the carrier of (Polynom-Ring (Polynom-Ring (n,R))) ; :: thesis: A . x = B . x
then reconsider x9 = x as Polynomial of (Polynom-Ring (n,R)) by POLYNOM3:def 10;
( A . x in the carrier of (Polynom-Ring ((n + 1),R)) & B . x in the carrier of (Polynom-Ring ((n + 1),R)) ) by ;
then reconsider Ax = A . x, Bx = B . x as Polynomial of (n + 1),R by POLYNOM1:def 11;
now :: thesis: for b being object st b in Bags (n + 1) holds
Ax . b = Bx . b
let b be object ; :: thesis: ( b in Bags (n + 1) implies Ax . b = Bx . b )
assume b in Bags (n + 1) ; :: thesis: Ax . b = Bx . b
then reconsider b9 = b as Element of Bags (n + 1) ;
reconsider p2 = x9 . (b9 . n) as Polynomial of n,R by POLYNOM1:def 11;
n < n + 1 by NAT_1:13;
then reconsider bn = b9 | n as Element of Bags n by Th3;
thus Ax . b = p2 . bn by A37
.= Bx . b by A38 ; :: thesis: verum
end;
hence A . x = B . x by FUNCT_2:12; :: thesis: verum
end;
hence A = B ; :: thesis: verum